An introduction to mathematical modeling : a course in mechanics - Oden, J. Tinsle [ (John Tinsley)] , 1936- (Hoboken, New Jersey : Wiley, 2011)
"An important resource, this book provides a short-course in nonlinear continuum mechanics, contains a brief account of electromagnetic wave theory and Maxwell's equations as well as an introductory account of quantum mechanics, and presents a brief introduction to statistical mechanics of systems in thermodynamic equilibrium. Also included is information on continuum mechanics, electrodynamics, quantum mechanics, and statistical mechanics"--Provided by publisher.
"An important resource, this book provides a short-course in nonlinear continuum mechanics, contains a brief account of electromagnetic wave theory and Maxwell's equations as well as an introductory account of quantum mechanics, and presents a brief introduction to statistical mechanics of systems in thermodynamic equilibrium. Also included is information on continuum mechanics, electrodynamics, quantum mechanics, and statistical mechanics. The author approaches mechanics as the branch of physics and mathematical science concerned with describing the motion of bodies, including their deformation and temperature changes, under the action of forces, and if the study of the propagation of waves and the transformation of energy in physical systems are added, then the term mechanics does indeed apply to everything that is covered within the book. "--Provided by publisher.
1. Nonlinear continuum mechanics -- 2. Electromagnetic field theory and quantum mechanics -- 3. Statistical mechanics
Includes bibliographical references (p. 317-323) and index
Keywords: Mechanics, Analytic